Social inclusion exclusion, gender politics and tribal women : A study on selected Maoist affected district of West Bengal - Taraphdar, Sampa (New Delhi : ICSSR)
This study has focused particularly, on the process of social inclusion exclusion of the studied tribal population from a gender perspective. In addition, as Levitas (2005) has commented 'Social exclusion is embedded in different discourses' and Wazed (2012) has opined that social exclusion intertwined with both material (economy, education, health) and discursive(personal, socio-cultural, identity and political aspect) perspective, the present study has discussed both the perspectives for analyzing the social exclusion and inclusion of tribal women.
Include bibliographical references.
Indian Council of Social Science Research.
English
Keywords: Social Exclusion -- Social Inclusion -- Tribe -- Maoist Movement -- West Bengal - India